The Impact Of Polygamy Marriage Practices on the Family - Dendik Irawan; Budi Parmono; Moh. Muhibbin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze polygamy practices and their positive and negative impacts on family life as well as the psychological conditions of wives and children in the community of Paciran District, Lamongan Regency. This research employs a qualitative approach, with a conceptual and case study design. Data were collected through in-depth interviews, observations, and documentation involving polygamy practitioners, community leaders, and related parties. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that polygamy practices in Paciran vary, ranging from open to covert arrangements. Normatively, polygamy is perceived as permissible in Islamic law under strict conditions of justice and financial capability. However, in practice, polygamy tends to generate more negative impacts than positive ones, particularly affecting the psychological well-being of wives and children, including jealousy, emotional instability, domestic conflict, and declining family harmony. Nevertheless, a limited number of families demonstrate relative stability through equitable treatment and effective communication. This study highlights that polygamy requires strong psychological, economic, and moral readiness to prevent broader social and familial harm.